Acquiring the Art of Conducting: Deliberate Practice as Part of Professional Learning - Schmidt Simon; Längler Manuel; Altenbuchner Amelie; Kobl Louisa; Gruber Hans (SAGE PUBLICATIONS INC, 2025)
Research was and still is involved in the controversial issue about innate talent or extensive practice as the determinants of excellent performance in a range of domains. This study aims to contribute by presenting an analysis of practice activities in a domain that appears to be particularly suitable-orchestral conducting. Most conductors usually attain expertise in instrument playing prior to commencing conducting studies. Twenty-seven students of German study programs of orchestral conducting (approximately 18.7% of the population) responded to a questionnaire about their practice activities in conducting programs and their instrumental experiences. Descriptive results show the wealth of prestudy experiences conducting students have. A clear influence on practice activities cannot be stated. During study, students rated conducting-specific practice activities as more demanding and devoted more time to them than to general music practice activities. Therefore, conducting-specific practice activities might have been practiced more deliberately than general music practice activities.